Effect of a pre-aging treatment on the mechanical behaviors of Ni50.3Ti49.7 − xHfx (x ≤ 9 at.%) Shape memory alloys. (1st April 2018) - Amin-Ahmadi, Behnam; Gallmeyer, Thomas; Pauza, Joseph G.; Duerig, Tom W.; Noebe, Ronald D.; Stebner, Aaron P.
Abstract: Transmission electron microscopy and mechanical testing were used to determine the effect of pre-aging (300 °C for 12 h) on microstructure and mechanical behavior of a series of Ni50.3 Ti49.7 − x Hfx shape memory alloys (x = 6, 8, 8.5, 9 at.%) prior to normal aging at 550 °C for 3.5 h. Pre-aging was found to promote homogenous nucleation of nanosized H-phase precipitates, resulting in improved mechanical stability and strength and 4% recoverable compression strain without permanent deformation. The absence of pre-aging generally resulted in heterogeneous formations of larger H-phase precipitates, primarily clustered along grain boundaries, and correlated with poorer mechanical behavior. Graphical abstract: Image 1